(untitled) (Research, Society and Development, 2022)
The present study aimed to review aspects that may be related to conceptions about BI, the practice of physical exercises, bullying and eating disorders (ED) in adults. This is a systematic review. A search for articles on the topic, published between January 1st, 2016, and October 8th, 2021, was carried out in the database “Portal Periódicos da Capes”, being selected articles that corresponded to the proposed them, with the exclusion of all those that were bibliographic reviews, other types of review, books, theses, dissertations, and studies that did not cover the chosen topic. Fourteen articles were selected. In general, these articles indicated a high rate of adult individuals dissatisfied with their BI, mostly female, who sought to reduce their silhouettes, while male individuals wanted to increase their body mass. Associations between body image estimation and variables such as exercise, signs of ED, diseases and/or depressive symptoms, distortions in body image, lifestyle and others, were mentioned, without establishing a relationship between these negative perceptions and risks of bullying and related disorders which may have been experienced in adolescence. A great influence of the media, family, friends and socially established standards on the perception that individuals hold about their body image has been reported. In this context, it is necessary to deconstruct the image of a perfect standard body by the media itself and spaces such as schools and family environment, preventing the multiplication of BI distortion, ED and consequent depression.